(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The research aims to define the role of Entre Premeurship in enhancing the quality of hotel service in the four and five star hotels in the city of Latakia, by studying the relationship between leadership and the dimensions of hotel service quality (tangibility, reliability, response, sympathy, and guarantee). The researcher relied on the descriptive analytical method, and the research community included all the administrative officials (director, assistant, head of department) in the four-star and five-star hotel organizations in Lattakia, and the research sample is a soft random sample of (100) managers, where the questionnaire was distributed The search tool on them, (91) a valid and complete questionnaire was retrieved for statistical analysis. The search community also included all customers of the four and five-star hotels in Lattakia, where the researcher obtained responses (91) customers to know the quality of the hotel service provided to them from those hotels . The research reached a set of results, the most important of which are: The hotels in question seek to lead towards leadership in their business, with relative importance (77.23%), by responding to situations of change and keeping pace with developments in the business environment, developing creative ideas and taking risks and taking bold stances and developing resources creatively . The results also showed that there is a direct relationship and statistical function between the orientation of the hotels in question towards leadership in their business and the enhancement of the quality of the hotel service through its dimensions.